2022
DOI: 10.1021/acs.est.2c06321
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Particles Are Major Sources of Aged Anthropogenic Organic Carbon in Marginal Seas

Abstract: Deposition of atmospheric particulates is a major pathway for transporting materials from land to the ocean, with important implications for climate and nutrient cycling in the ocean. Here, we report the results of year-round measurements of particulate organic carbon (POC) and black carbon (BC) in atmospheric aerosols collected on Tuoji Island in the coastal Bohai-Yellow Sea of China (2019–2020) and during a cruise in the western North Pacific. Aerosol POC contents ranged from 1.9 to 11.9%; isotope values ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…Plot of (a) δ 13 C vs Δ 14 C values for solid-phase SBC and porewater DBC in the surface sediments of the Yangtze and Yellow River estuaries; the end-member values of different BC sources are shown. (b) Comparative plot of the carbon isotope values of BC in sediment, river, and atmospheric particles dissolved in river and estuarine sediment porewater (data are referenced from ,, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plot of (a) δ 13 C vs Δ 14 C values for solid-phase SBC and porewater DBC in the surface sediments of the Yangtze and Yellow River estuaries; the end-member values of different BC sources are shown. (b) Comparative plot of the carbon isotope values of BC in sediment, river, and atmospheric particles dissolved in river and estuarine sediment porewater (data are referenced from ,, ).…”
Section: Discussionmentioning
confidence: 99%
“…In our recent study, we collected atmospheric aerosol particles on Tuoji Island in the coastal Bohai-Yellow Sea of China for one year and found that 19–66% of the atmospheric POC comprised PBC with low Δ 14 C values (−544 ± 96‰, 7000 years), as 43% was produced from fossil fuel combustion. Thus, it can be concluded that atmospheric deposition is a significant source of aged anthropogenic OC in the marginal seas of China . After this PBC from rivers and the atmosphere is deposited into the estuarine and coastal sediments, the recently generated biomass-derived BC gradually degraded, dissolved into the porewater as DBC, and left the fossil material-derived BC, which was preserved in the solid phase as SBC; thus, the 14 C ages of the SBC became older than the PBC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Particulate matter (PM), which coexists with various chemical and physical substances, is one of the atmospheric pollutants. 2 Owing to their large specific surface area and strong adsorption, atmospheric aerosol particles can absorb a large number of viruses, bacteria, nitrogen oxides, polycyclic aromatic hydrocarbons, and heavy metals in the atmosphere, 3,4 which can be inhaled into human alveoli and deposited during long-term exposure, posing health risks to humans. 5 Even though routine analytical techniques for particles have perfect detection sensitivity and accuracy, they are not conducive to the online and rapid analysis of metal elements in atmospheric aerosol particles, because these techniques involve expensive instruments and complex sample pretreat- ment and are labor-intensive.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Particulate matter (PM), which coexists with various chemical and physical substances, is one of the atmospheric pollutants . Owing to their large specific surface area and strong adsorption, atmospheric aerosol particles can absorb a large number of viruses, bacteria, nitrogen oxides, polycyclic aromatic hydrocarbons, and heavy metals in the atmosphere, , which can be inhaled into human alveoli and deposited during long-term exposure, posing health risks to humans …”
Section: Introductionmentioning
confidence: 99%